1 Peter - Jobes, Karen H. (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2022)
"A leading evangelical biblical scholar offers a substantive evangelical commentary on 1 Peter in the award-winning BECNT series"--
Introduction to 1 Peter -- A greeting to the Christian diaspora of Asia Minor (1:1-2) -- The opening of the letter : reassurance for God's people (1:3-2:10) -- As God's people, live godly lives (2:11-4:11) -- Consolation for the suffering flock (4:12-5:11) -- The letter closing : final words and greetings (5:12-14) -- Excursus : the syntax of 1 Peter : how good is the Greek?
Includes bibliographical references and index.
Keywords: Bible. -- Commentaries; Commentaries